HUBUNGAN RELIGIUSITAS TERHADAP AGRESIVITAS REMAJA DI MADRASAH ALIYAH ASSALAAM TEMANGGUNG - Abdul Ghofur; Siti Hafsah Budi Argiati (Universitas Sarjanawiyata Tamansiswa, 2012)
ABSTRACTThe aim of this study was finding the relationship between religiosity and adolescent aggressiveness at Madrasah Aliyah Assalaam Temanggung. The instruments are the religiosity scale and aggressiveness scale. Data was collected from 100 adolescence subjects ages 16-18 years, sitting in class X and XI MA Assalaam. Data analysis techniques used Pearson Product Moment Correlation (2-tailed). The result showed that the correlation coefficients obtained for (r) = -0.468 with a significance level of 0.000 (p <0.01). The conclusion, there is a negative significant relationship between religiosity to adolescent aggressiveness. The negative coefficient showed correlation to the both variables was negative. This means that increasing religious level can make decreasing aggression level, and converse, decreasing religious level can make increasing aggression level. Thus, the hypothesis in this study is acceptable.Â Keywords: religiosity, aggressiveness, adolescence